In-situ preparation of porous carbon nanosheets loaded with metal chalcogenides for a superior oxygen evolution reaction. (August 2019) - Du, Yang; Khan, Shaukat; Zhang, Xingcai; Yu, Guofang; Liu, Ruliang; Zheng, Bingna; Nadimicherla, Reddeppa; Wu, Dingcai; Fu, Ruowen
Abstract: Nowadays, it has been more and more important to ingeniously design sheet-like structures since the performance of many modern materials fundamentally depends upon the exploitation of these structures. In this work, we have successfully developed a facile and effective strategy for fabricating a class of 2D porous carbon nanosheets that simultaneously exhibit high surface areas and uniform distribution of metal chalcogenides for superior oxygen evolution reaction. The synthesis of these 2D carbon nanosheets involves the in-situ metal ion adsorption and exchange by the sulfonate radicals of polymer sheets followed by carbonization to form a series of metal chalcogenides loaded porous carbon nanosheets (PCNs/Mx Sy ). The abundant mesopores (e.g., 3–7 nm, 524 m 2 g −1 ) that derived from the spontaneous stacking of flexible GO precursor are advantageous to the exposure of heteroatom sites. The uniform catalytic sites (33.8 nm) formed in-situ effectively avoid the agglomeration of functional components, which are conducive to make full use of catalytic sites and consequently shows excellent OER performance. We hope that our novel strategy can open a new door for the application and innovation of fabricating 2D porous carbon nanosheets in a wide range of areas including energy storage, adsorption, catalysis, separation and so on. Graphical abstract: Image 1